Solid Organ Transplantation in Infants and Children (Organ and Tissue Transplantation, 2018)
A new textbook of transplantation for infants and children is needed that is at least a first effort at achieving standard work in this field. Solid Organ Transplantation in Infants and Children provides a broad view of the current practice of solid organ transplantation in pediatric patients. It focuses on best practice and measureable outcomes whenever possible. It provides direct guidance for standard work in this broad and young field of clinical work. It portrays the regulatory environment in which this work occurs and the specific program requirements for each clinical program. Organized in two volumes, the first volume is devoted to the pediatric patient and their particular needs or concerns. This volume also contains information on the regulatory environment and pediatric program specific requirements. The second volume is devoted to the standard work in each solid organ transplanted. These volumes will be very useful for every practicing pediatric transplant program in the United States and Canada and much of the developed world. By reading these volumes, the reader will gain a firm understanding and practical knowledge of standard work in solid organ transplantation and the regulatory environment and requirements of programs to do that work.